Pomensko-skladenjski premiki v briškem in nadiškem narečju - Zuljan Kumar, Danila (Jezik in slovstvo, 2002)
Some types of semantico-syntactic shifts in the dialects of Brkini! and Nadiža and their origins are presented. The presentation is limited to verbs, mainly to rhematic verbs, in which these changes were the most pronounced. It is concluded that a majority of these shifts occurred under the influence of the neighbouring Romance language group, while a few happened also witin system of the Slovene language.
Keywords: Slovene; slovenščina; Slovene dialects; slovenska narečja; briško narečje; nadiško narečje; Brda; Nadiža; Natisone; dialectology; dialektologija; semantics; semantika; sintaksa